Effect on Swimming Start Performance of Two Types of Activation Protocols: Lunge and YoYo Squat. Issue 3 (March 2015) - Cuenca-Fernández, Francisco; López-Contreras, Gracia; Arellano, Raúl
Abstract : Abstract: Cuenca-Fernández, F, López-Contreras, G, and Arellano, R. Effect on swimming start performance of two types of activation protocols: Lunge and YoYo squat. J Strength Cond Res 29(3): 647–655, 2015—The purpose of this study was to compare the effects of 2 protocols of postactivation potentiation (PAP) on swimming start perfomance (SS). Fourteen trained swimmers (10 men and 4 women) volunteered for this study. An intragroup design of randomized repetitive measurements was applied. A previous SS trial, performed after a standard warm-up (SWU), served as a reference. Two methods of PAP, performed after 1 hour of rest, were randomly added to the SWU: (a) 3 lunges at 85% of 1 repetition maximum (LWU) and (b) 4 repetitions on the flywheel device YoYo squat (YWU). Swimmers were tested in an SS 8 minutes after the PAP warm-ups. Kinematic variables were collected using 3 underwater digital video cameras fixed poolside and operating at 25 Hz, and 1 high-speed camera focused on the block and operating at 300 Hz. Data obtained from the video analysis were processed using a repeated measures analysis of the variance. The mean horizontal velocity of the swimmer's flight improved after both PAP methods, with the greatest improvement after YWU ( F 2, 12 = 47.042, p < 0.001; SWU = 3.63 ± 0.11; LWU = 4.15 ± 0.122; YWU = 4.89 ± 0.12 m·s −1 ). After YWU, it took the subjects less time to cover a distance of 5 m ( F 2, 12 = 24.453, p < 0.001) and 15 m ( F 2, 12 = 4.262, p < 0.04). Subjects also achieved a higher mean angular velocity of the knee extension ( F 2, 12 = 23.286, p < 0.001) and a reduction of the time on the block ( F 2, 12 = 6.595, p ⩽ 0.05). These results demonstrate that muscle performance in the execution of an SS is enhanced after a warm-up with specific PAP protocols. YWU leads to the greatest improvement in the performance of the swimmer's start and, therefore, may be especially beneficial in short events.